Consensusability of continuous‐time multi‐agent systems with general linear dynamics and intermittent measurements. Issue 6 (1st April 2013) - Gao, Yanping; Ma, Jingwei; Zuo, Min; Mo, Lipo; Yu, Junyan
Abstract : This article studies the consensusability of multi‐agent systems with general linear continuous‐time dynamics. It is assumed that each agent can only obtain the information of other agents at sampling instants. Some sufficient and necessary conditions for consensusability in the case of state feedback are established, and it is shown that multi‐agent systems with periodic sampling are consensusable if and only if the system associated with each agent is stabilisable and the topology graph has a spanning tree. Furthermore, some methods are provided to seek controller gain and sampling period which ensure consensus. Simulations are performed to validate the theoretical results.